2021
DOI: 10.1101/2021.01.08.426007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of Fara-darmani Consciousness Field on Bacterial Population Growth

Abstract: The treatment of bacterial infections and the rising challenges of antibiotics resistance are global concerns and the primary topics in basic science and clinical microbiology. In the present study, the effectiveness of treatment of selected populations of bacteria using an immaterial and non-energetic method called Fara-darmani Consciousness Field treatment is investigated. Population growth was assessed by turbidimetry, colony counting and tetrazolium chloride reduction assays in non-treated control and Fara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…However, no significant change was observed in the samples that were affected by the Fields compared to the earth's gravity. In a previous study, the effect of T-Consciousness Field 1 or Faradarmani on the growth of bacterial population has been confirmed (6). In the present experiment, bacteria were simultaneously affected by three types of T-Consciousness Fields, and it was found that under the influence of these Fields, they grew less in microgravity conditions.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…However, no significant change was observed in the samples that were affected by the Fields compared to the earth's gravity. In a previous study, the effect of T-Consciousness Field 1 or Faradarmani on the growth of bacterial population has been confirmed (6). In the present experiment, bacteria were simultaneously affected by three types of T-Consciousness Fields, and it was found that under the influence of these Fields, they grew less in microgravity conditions.…”
Section: Resultssupporting
confidence: 79%
“…For this reason, several studies have been conducted to investigate their effects on the food chain and its long-term harm (5). Various techniques are used to remove these pollutants, including non-biological methods such as electrochemical technologies and bioremediation methods that rely on the use of microorganisms (6).…”
Section: Microorganismsmentioning
confidence: 99%
“…The sera of each group was mixed (pooled) at each stage of blood sampling. In In previous studies, the effects of the TCFs on MCF7 cancer cell line (Taheri et al, 2020a), Alzheimer's disease rat models (Taheri et al, 2021b), spatial memory, and avoidance behavior of a rat model of Alzheimer's disease (Taheri et al, 2021c), wheat plant (Torabi et al 2020), bacterial population growth (Taheri et al, 2021d), viral growth (Taheri et al 2021a), and the electrical activity of the brain during Faradarmani in the Faradarmangars population have been investigated (Taheri et al, 2020b).…”
Section: Serum Neutralization and Elisa Testsmentioning
confidence: 99%
“…1 ‫پاالیی‬ ‫هــایزیســت‬ ‫راه‬ ‫شــود(6).درایــنمطالعــه،ابتــدااثرگــذاری‬ ‫اســت،بــهکارگرفتــهمی‬ ‫هــایشــعوریطاهــری(‪)TCFs‬بــررشــد‬ ‫ترکیــبســهنــوعازمیدان‬ ‫ی12‪BL‬درشــرایط‪MG‬مــورد‬ ‫باکتــریاشریشــیاکــوالی،ســویه‬ ‫ـر‬ ‫ـریبـ‬ ‫ـشدیگـ‬ ‫ـج،آزمایـ‬ ‫ینتایـ‬ ‫ـاهده‬ ‫ـسازمشـ‬ ‫ـتوپـ‬ ‫ـرارگرفـ‬ ‫ـیقـ‬ ‫بررسـ‬ ‫ـربدر‬ ‫ـزسـ‬ ‫ـذففلـ‬ ‫ـرویزیهدرحـ‬ ‫ـسسـ‬ ‫ـتیساکارومایسـ‬ ‫ـذبزیسـ‬ ‫ـارجـ‬ ‫رفتـ‬ ‫هــا‬ ‫دومحیــطگرانــشزمیــن(‪)1G‬و‪MG‬تحــتتاثیــرایــنمیدان‬ ‫ـد.‬ ‫ـیشـ‬ ‫طراحـ‬ ‫ها‬ ‫روش‬ ‫و‬ ‫مواد‬ ‫طاهــری:بــاتوجــهبــه‬ ‫شــعوری‬ ‫هــای‬ ‫میدان‬ ‫کارگیــری‬ ‫به‬ ‫ـت‬ ‫ـاتحـ‬ ‫هـ‬ ‫ـماره،نمونه‬ ‫ـنشـ‬ ‫ـاتایـ‬ ‫ـشمالحظـ‬ ‫ـدهدربخـ‬ ‫شـ‬ ‫ـاتارائه‬ ‫توضیحـ‬ ‫هــاقــرارگرفتنــد.‬ ‫تاثیــرایــنمیدان‬ ‫باکتری‬ ‫کشت‬ ‫محیط‬ ‫ی12‪BL‬اشریشــیاکــوالیبــااســتفادهازمحیــطکشــت‬ ‫ابتــداســویه‬ ‫کشــتدادهشــدکــهایــنمحیــط‬ Lurria-Bertani ‫مایــع)‪(LB‬‬ ‫لیتــر):یــکگــرمپپتــون(‪،)QUELAB‬‬ ‫شــامل(درهــر001میلی‬ ‫ـرک،‬ ‫ـرم‪(NaCl‬مـ‬ ‫ـکگـ‬ ‫)،یـ‬QUELAB(‫ـر‬ ‫یمخمـ‬ ‫ـاره‬ ‫ـرمعصـ‬ ‫5/0گـ‬ ‫ـت‬ ‫ـطکشـ‬ ‫ـریدرمحیـ‬ ‫ـتوکباکتـ‬ ‫ـرازاسـ‬ ‫ـجمیکرولیتـ‬ ‫ـپسپنـ‬ ‫ـود.سـ‬ ‫ـان)بـ‬ ‫آلمـ‬ ‫ســیلینکشــتشــدودرانکوباتــور‬ ‫مایــع‪LB‬بــاپنــجمیکرولیتــرآمپی‬ ‫ـاعت‬ ‫ـا81سـ‬ ‫ـدت61تـ‬ ‫ـهمـ‬ ‫گراد،بـ‬ ‫ـانتی‬ ‫یسـ‬ ‫ـه‬ ‫ـای73درجـ‬ ‫ـیکرداردردمـ‬ ‫شـ‬ ‫ـد.‬ ‫ـهشـ‬ ‫انکوبـ‬ ‫میکروگراویتی‬ ‫اعمال‬…”
unclassified
“…‫ـد‬ ‫ـررشـ‬ ‫ـی،بـ‬ ‫ـافرادرمانـ‬ ‫ـعوری(ط)1یـ‬ ‫ـدانشـ‬ ‫ـرمیـ‬ ‫ـیتاثیـ‬ ‫یقبلـ‬ ‫ـه‬ ‫درمطالعـ‬ ‫ـا‬ ‫هـ‬ ‫ـر،باکتری‬ ‫ـشحاضـ‬ ‫ـت(6).درآزمایـ‬ ‫ـدهاسـ‬ ‫ـدشـ‬ ‫ـیتاییـ‬ ‫ـتباکتریایـ‬ ‫جمعیـ‬ ‫زمــانتحــتتاثیــرســهنــوعمیــدانشــعوری(ط)بودنــدو‬ ‫طــورهم‬ ‫به‬ ‫تــریدرشــرایط‬ ‫هــارشــدکم‬ ‫مشــخصشــدتحــتتاثیــرایــنمیدان‬ ‫میکروگراویتــیداشــتند.باکتــریایکــوالی،بخشــیازفلــورنرمــال‬ ‫شــدهاســت.‬ ‫یشناخته‬ ‫انســانبــودهوالبتــهبهتریــنموجــودزنــده‬ ‫ـه‬ ‫ـبتبـ‬ ‫ـارانسـ‬ ‫ـدمـ‬ ‫ـقدیـ‬ ‫ـدافـ‬ ‫توانـ‬ ‫ـدلمی‬ ‫ـنمـ‬ ‫ـرایـ‬ ‫ـاتبـ‬ ‫ـن،مطالعـ‬ ‫بنابرایـ‬ ‫یآن‬ ‫ـوه‬ ‫ـراتبالقـ‬ ‫ـیوخطـ‬ ‫ـرایطمیکروگراویتـ‬ ‫اشدرشـ‬ ‫ـی‬ ‫هایاحتمالـ‬ ‫ـخ‬ ‫پاسـ‬ ‫یفضایــیوســعتبخشــد.گــزارششــدهاســت‬ ‫بــرایســالمتیخدمــه‬ ‫دهــد‬ ‫کــهمیکروگراویتــیتشــکیلبیوفیلــمایکــوالیراافزایــشمی‬ ‫(9).عــالوهبــرایکــوالی،آزمایــشمشــابهیبــرمــدلیوکاریــوت‬ ‫ـر‬ ‫ـنمخمـ‬ ‫ـتیایـ‬ ‫ـذبزیسـ‬ ‫ـارجـ‬ ‫ـدورفتـ‬ ‫ـامشـ‬ ‫ـرویزیهانجـ‬ ‫ـیسسـ‬ ‫ساکارومایسـ‬ ‫ـر‬ ‫ـدونتاثیـ‬ ‫ـاوبـ‬ ‫ـرایط‪MG‬و‪1G‬بـ‬ ‫ـربدرشـ‬ ‫ـنگینسـ‬ ‫ـزسـ‬ ‫ـذففلـ‬ ‫درحـ‬ ‫ـد.‬ ‫ـیشـ‬ ‫ـزبررسـ‬ ‫ـوع‪TCF‬نیـ‬ ‫ـهنـ‬ ‫سـ‬ ‫ـادر‬ ‫هـ‬ ‫ـریازآلودگی‬ ‫ـورجلوگیـ‬ ‫ـهمنظـ‬ ‫ـاتبـ‬ ‫ـنمطالعـ‬ ‫ـهایـ‬ ‫کـ‬ ‫ـراین‬ ‫ـالوهبـ‬ ‫عـ‬ ‫تــری‬ ‫توانــددرکعمیق‬ ‫هــایفضایــیحائــزاهمیــتاســت،می‬ ‫ماموریت‬ ‫ـاهده‬ ‫ـنمشـ‬ ‫ـن،ایـ‬ ‫ـد(11).همچنیـ‬ ‫ـمکنـ‬ ‫ـنفراهـ‬ ‫ـارجاززمیـ‬ ‫ـاتدرخـ‬ ‫ازحیـ‬ ‫کــهاعمــالمیــدانشــعوری(ط)باعــثشــداثــرالقــایرشــدمحیــط‬ ‫ـان‬ ‫ـدنشـ‬ ‫دهـ‬ ‫ـانمی‬ ‫ـود،نشـ‬ ‫ـارشـ‬ ‫ـوالیمهـ‬ ‫ـریایکـ‬ ‫ـرباکتـ‬ ‫ـیبـ‬ ‫میکروگراویتـ‬ ‫ـوردرک‬ ‫ـهمنظـ‬ ‫ـت.بـ‬ ‫ـشاسـ‬ ‫ـتقلازگرانـ‬ ‫ـامسـ‬ ‫هـ‬ ‫ـنمیدان‬ ‫ـرایـ‬ ‫ـداثـ‬ ‫دهـ‬ ‫می‬ ‫تــری‬ ‫هــایشــعوری(ط)مطالعــاتبیش‬ ‫ســازوکاراثرگــذاریایــنمیدان‬ ‫عنــوانمثــالدرایــنآزمایــش،کاهــشجــذبزیســتی‬ ‫نیــازاســت.به‬ ‫ـت‬ ‫ـخصاسـ‬ ‫ـننامشـ‬ ‫ـشزمیـ‬ ‫ـربدرگرانـ‬ ‫ـنگینسـ‬ ‫ـزسـ‬ ‫ـذففلـ‬ ‫ـردرحـ‬ ‫مخمـ‬ ‫شــوداثــر‬ ‫تــردارد.بنابرایــن،پیشــنهادمی‬ ‫هــایبیش‬ ‫ونیــازبــهآزمایش‬ ‫ـوتدر‬ ‫ـوتویوکاریـ‬ ‫ـایپروکاریـ‬ ‫هـ‬ ‫ـارمدل‬ ‫ـررفتـ‬ ‫ـعوری(ط)بـ‬ ‫ـایشـ‬ ‫هـ‬ ‫میدان‬ ‫ـود.‬ ‫ـیشـ‬ ‫ـزبررسـ‬ ‫ـینیـ‬ ‫ـیوهایپرگراویتـ‬ ‫ـرایطمیکروگراویتـ‬ ‫شـ‬ ‫کازمــــوایـــــنتــل‬ ‫شــعور(ط)‬…”
unclassified